Uresničevanje odgovornosti zaščititi - Sancin, Vasilka (Javna uprava, 2023)
The international scientific conference Responsibility to Protect in Theory and Practice, held on 11 and 12 May 2023 at the Faculty of Law of the University of Ljubljana, marked the tenth anniversary of the launch of the series of biennial international interdisciplinary scientific conferences on the R2P principle at the Faculty of Law of the University of Ljubljana, which brings together theoreticians, researchers and practitioners from various fields relevant to the implementation of R2P from all over the world. Realisation of R2P requires working at multiple levels on all three pillars of the R2P principle. Attempts to manipulate it must be prevented and abuse to justify illegal practices must be condemned in the strongest possible terms.
Keywords: crimes against humanity; ethnic cleansing; etnično čiščenje; genocid; genocide; hudodelstva zoper človečnost; Mednarodno pravo; Pravna fakulteta Univerze v Ljubljani; responsibility to protect; University of Ljubljana Faculty of Law; vojne; war crimes